REverSe TRanscrIptase chain termination (RESTRICT) for selective measurement of nucleotide analogs used in HIV care and prevention. Issue 1 (14th July 2022) - Olanrewaju, Ayokunle O.; Sullivan, Benjamin P.; Gim, Alicia H.; Craig, Cosette A.; Sevenler, Derin; Bender, Andrew T.; Drain, Paul K.; Posner, Jonathan D.
Abstract: Sufficient drug concentrations are required for efficacy of antiretroviral drugs used in HIV care and prevention. Measurement of nucleotide analogs, included in most HIV medication regimens, enables monitoring of short‐ and long‐term adherence and the risk of treatment failure. The REverSe TRanscrIptase Chain Termination (RESTRICT) assay rapidly infers the concentration of intracellular nucleotide analogs based on the inhibition of DNA synthesis by HIV reverse transcriptase enzyme. Here, we introduce a probabilistic model for RESTRICT and demonstrate selective measurement of multiple nucleotide analogs using DNA templates designed according to the chemical structure of each drug. We measure clinically relevant concentrations of tenofovir diphosphate, emtricitabine triphosphate, lamivudine triphosphate, and azidothymidine triphosphate with agreement between experiment and theory. RESTRICT represents a new class of activity‐based assays for therapeutic drug monitoring in HIV care and could be extended to other diseases treated with nucleotide analogs.